Penguatan Kompetensi Guru PAUD dalam Penggunaan Media Pembelajaran Digital Berbasis Asset-Based Community Development (ABCD) di PAUD Ath-Thoyyibah Desa Pangadegan - Muhammad Toha; Ika Rustika Zaenah; Nisa Munajiyah; Dian Laili Rahmah; Siti Zulfa Laeliyah Bilqis Tadzkir Putri; Siti Lestari N. (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation in education requires Early Childhood Education (ECE) teachers to develop competencies in utilizing digital-based learning media. However, in rural ECE contexts, the use of technology remains limited due to the lack of contextual and sustainable training. This community service program aims to enhance the digital learning media competencies of teachers at PAUD Ath-Thoyyibah in Pangadegan Village through the Asset-Based Community Development (ABCD) approach. The program was implemented through stages of community asset mapping, collaborative action planning, practice-based training, and post-training mentoring and reflection. The results indicate that ECE teachers were able to develop simple digital learning media based on images, videos, and audio tailored to early childhood characteristics. In addition to improving technical skills, the program increased teachers’ self-confidence and fostered collaborative networks within the educational community. These findings demonstrate that the ABCD approach is effective in strengthening ECE teacher capacity by emphasizing local asset utilization and active community participation. This program contributes to improving the quality of early childhood learning and strengthening adaptive educational communities in response to technological development.